Subclinical thyroid disease in elderly subjects - Ceresini, Graziano; Morganti, Simonetta; Maggio, Marcello; Uberti, Elisa; Fiorino, Ilaria; Artoni, Andrea; Teresi, Giulio; Belli, Serena; Ridolfi, Valentina; Valenti, Giorgio; Ceda, Gian Paolo (Acta Biomedica Atenei Parmensis, 2010)
Subclinical thyroid disease (STD) is defined as circulating concentrations of free T4 and free T3 within their respective reference ranges in the presence of abnormal circulating concentrations of TSH. SCD is being diagnosed more frequently in clinical practice and is reported to be more prevalent in elderly as compared to young or adult subjects. The clinical impact of subclinical thyroid dysfunction is still a matter of debate, although it has been associated with various negative clinical outcomes, such as increased cardiovascular risk, reduction in bone density, decline in cognitive function, and increased risk of overt thyroid dysfunction. The treatment of STD is controversial and there is no consensus on the TSH cutoff values which can be used as indicators for treatment, especially in elderly subjects. In the present review, we report data on the prevalence of STD and on the potential clinical consequences of these disorders. Also, data of the Literature regarding the issue of the treatment of STD in relation to the age of the patient are reported.